Voltage Instability of Initiation Fault Duration as Influenced by Nodes Short Circuit Levels NSCL with Different Types of Loads - Youssef Ahmed Mobarak; Mahmoud M. Hussein (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The occurrence of voltage instabilities or voltage collapses depend on the duration of the persistence of the fault and on the type of fault, some faults lead to voltage instabilities, others lead to voltage collapse. Evaluation of fault durations causing occurrence of voltage instabilities is the main goal of this paper. This paper searches for the effect of nodes short circuit levels NSCL and its duration periods initiation of voltage instability, with lagging and leading load power factors at certain loads buses. In this paper, the power system dynamic simulation program is developed for dynamic analysis of voltage stability. This paper is concerned with the fault duration which lead to the occurrence of voltage instability phenomena due to NSCL. The fault which lead to voltage instability is found to be short circuits at certain nodes cleared without any variation in the transmission system elements, i.e. the post-fault conditions will be the same as the pre-fault conditions. Models for loads considered in this study are induction motors with three different shaft mechanical loads, constant impedance CZ loads, constant current CI loads and constant power CP loads are used, as they depict the behavior of most power system loads. The influence of the transmission network impedances, which are nearly the inverse of the NSCL, on the fault duration which lead to the occurrence of voltage instabilities are studied and evaluated using various load representations.